2017
DOI: 10.1016/j.jmacro.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Bank capital, the state contingency of banks’ assets and its role for the transmission of shocks

Abstract: Reproduction permitted only if source is stated.ISBN 978 -3-95729-064-9 (Printversion) Non-technical summary Research QuestionRecent macroeconomic models heavily emphasize the role of bank capital as a propagation channel of shocks which results from a financial contracting problem between banks and their creditors and amplifies shocks to the real economy. Since bank capital is an important determinant of banks' leverage, which in turn affects how shocks are propagated through the banking sector to the real e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…In the same vein, this study established that bank asset exact a direct influence on stock price with the implication that as a bank asset size increase, its will compel an increasing trend in its stock prices. This submission is in line with the views of Hoechle, Schmid, Walter & Yermack (2012), Blau, Brough & Griffith (2017) and Kühl (2017) as increase in firm asset and capital often compels changes in its shares to several factors such as managerial self-interest which makes it possible to channel internal cash flows to the most profitable investment outlet. Similarly, increased asset size aids diversification across sectors which improve monitoring incentives, reduces returns dispersion and shrink risk shifting benefits.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the same vein, this study established that bank asset exact a direct influence on stock price with the implication that as a bank asset size increase, its will compel an increasing trend in its stock prices. This submission is in line with the views of Hoechle, Schmid, Walter & Yermack (2012), Blau, Brough & Griffith (2017) and Kühl (2017) as increase in firm asset and capital often compels changes in its shares to several factors such as managerial self-interest which makes it possible to channel internal cash flows to the most profitable investment outlet. Similarly, increased asset size aids diversification across sectors which improve monitoring incentives, reduces returns dispersion and shrink risk shifting benefits.…”
Section: Discussionsupporting
confidence: 82%
“…The analysis result showed that net profit margin, return on assets has got significant positive impact on stock returns while earnings per share has got significant negative impact on stock returns. Kühl (2017) examines the evolution of bank capital based on the share of non-state-contingent assets in banks' balance sheets and implications for macroeconomic dynamics using a new Keynesian dynamic general equilibrium model in order to gain an insight into how this composition affects shocks transmission in the economy. The results showed that shocks transmission to the real economy is caused by financial frictions in the banking sector is reduced as the size of non-state-contingent assets in banks' balance sheets increases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The analytical result showed that net profit margin and return on assets had positive and significant influence on stock returns while earnings per share had negative influence on stock returns. Kühl (2017) examined the advancement in bank capital based on the proportion of non-state-contingent assets in their statement of financial position and implications for general economic changes using a new Keynesian dynamic general equilibrium model. The results showed that shocks' transmission to real GDP is created by banking sector frictions that reduced as the size of nonstate-contingent assets increases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The analytical result showed that net profit margin and return on assets had positive and significant influence on stock returns while earnings per share had negative influence on stock returns. Kühl (2017) examined the advancement in bank capital based on the proportion of non-state-contingent assets in their statement of financial position and implications for general economic changes using a new Keynesian dynamic general equilibrium model. The results showed that shocks' transmission to real GDP is created by banking sector frictions that reduced as the size of nonstate-contingent assets increases.…”
Section: Literature Reviewmentioning
confidence: 99%